STUDI PENGARUH BACK FLASHOVER PADA SALURAN TRANSMISI 150 kV PAYAKUMBUH - KOTO PANJANG - Arfita Yuana Dewi; Yusreni Warmi; Peprizal Peprizal; Asnal Effendi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
Back flashover is one of the consequences of a direct lightning strike. Back flashover is caused by the higher grounding resistance value of the tower leg. Doing so can create an overvoltage and can cause damage to electrical equipment. One way to minimize overvoltage due to back flashover is to adjust the grounding resistance at the foot of the tower. Tower 10 has a grounding resistance value of the tower foot of 4.78 ohms, the total back flashover is 29.085544 times / year. Tower 50 has a grounding resistance value of the tower foot of 14 ohms and the number of back flashover disturbances is 85.0213544 times / year. In tower 10 the value of the grounding resistance of the tower feet is smaller than the value of the grounding resistance of the menra feet 50, so the total number of back flashovers on tower 50 is higher than tower 10. The greater the value of the grounding resistance of the tower feet, the higher the number of back flashovers. The average grounding resistance of the tower leg 1 - 249 Payakumbuh Koto Panjang has a value of 4.2847 ohm tower foot grounding resistance, the number of back flashover disturbances is 24.593635 times / year. The standard grounding resistance of the tower leg is 10 ohms, because tower 50 has a grounding pressure value exceeding the standard, which is 14 ohms, so that it can cause the number of back flashover disturbances to exceed the standard 13 times / 100 km / year.